Studies of equatorial F-region depletions and dynamics using multiple wavelength nightglow imaging - Mukherjee, G.K. (My University, 2003)
A charge coupled device based all-sky imaging system with 180° field of view has been operating at Kolhapur (16.8°N, 74.2°E, dip lat. 10.6°N) in India on clear moonless nights to study the dynamics of equatorial ionospheric irregularities by examining the images of three oxygen lines at OI 630, 557.7 and Full-size image (<1 K). The all-sky camera offers broad and instantaneous coverage of the movement of large-scale size ionospheric irregularities (depletions or bubbles) over a region of Full-size image (<1 K) at about Full-size image (<1 K) altitude. The location of the station is important as the single image at a given instant maps the irregularities over a large area extending from the geomagnetic equator to the equatorial ionization anomaly region. Several characteristics of irregularities discussed in this report were observed during ISTEP campaign periods conducted in March–April of 1998 and 1999. One example of the signature of simultaneous depletions observed in OI 630, 557.7 and Full-size image (<1 K) images is reported. Also, the signature of midnight temperature maximum (MTM) in OI 630 nm airglow has been presented. The tilt of the MTM structure with magnetic meridian was found to change during the course of its movement towards north. The eastward plasma drift speeds ranging from 0 to Full-size image (<1 K) computed from bubble movement matches well with the drift speeds computed from VHF scintillation experiments and Jicamarca radar observations.
Keywords: Equatorial spread-F; Depletion; MTM; Apex altitude; Equatorial Ionization anomaly; F-region